Development of instruments of higher order thinking skills (HOTS) for phase D students - Mildariah, Kurnila; Mainumah, Maimunah; Anggraini, Rini Dian (Universitas Maritim Raja Ali Haji, 2025)
This research aims to develop test instruments for Higher Order Thinking Skills (HOTS) that are validated, reliable, and possess excellent discrimination power, as well as appropriate levels of difficulty. These tools are intended to boost the advanced thinking abilities of students at phase D. According to the Organization for Economic Cooperation and Development (OECD) report on December 5, 2023, which analyzed the 2022 Program for International Student Assessment (PISA) scores in mathematics, including HOTS questions, there has been a notable worldwide decline. Specifically, Indonesia ranked 68th, with a math score of 379. The focus of this study is on developing HOTS test tools that address topics such as relations, functions, linear equations, and systems of two-variable linear equations, drawing from the AKM (Minimum Competency Assessment) and HOTS mathematics question books. The HOTS questions are designed to encompass cognitive levels C4 (analyzing), C5 (evaluating), and C6 (creating), following the revised Bloom's Taxonomy by Krathwohl and Anderson. As highlighted by the Ministry of Education, Culture, Research, and Technology (2022), the development of HOTS questions must include elements such as (1) incorporating stimuli and (2) presenting new contexts within the material or question formulation. The questions are constructed in essay format, adhering to standards for validity and reliability, as well as optimal difficulty and discrimination levels. This study employs a development model comprising two phases: the preliminary phase, which involves analysis and design, followed by the formative evaluation phase, encompassing self-evaluation, expert review, one-on-one sessions, small group interactions, and field tests. The outcome of this study produced 17 valid questions with a reliability coefficient of 0.848; 14 questions exhibited strong discrimination power, and 3 demonstrated adequate discrimination power, with all 17 HOTS questions classified in the medium difficulty range.